Development, behaviour and sensory processing in Marshall–Smith syndrome and Malan syndrome: phenotype comparison in two related syndromes. Issue 12 (9th October 2020) - Mulder, P. A.; van Balkom, I. D. C.; Landlust, A. M.; Priolo, M.; Menke, L. A.; Acero, I. H.; Alkuraya, F. S.; Arias, P.; Bernardini, L.; Bijlsma, E. K.; Cole, T.; Coubes, C.; et al.
Abstract: Background: Ultrarare Marshall–Smith and Malan syndromes, caused by changes of the gene nuclear factor I X ( NFIX ), are characterised by intellectual disability (ID) and behavioural problems, although questions remain. Here, development and behaviour are studied and compared in a cross‐sectional study, and results are presented with genetic findings. Methods: Behavioural phenotypes are compared of eight individuals with Marshall‐Smith syndrome (three male individuals) and seven with Malan syndrome (four male individuals). Long‐term follow‐up assessment of cognition and adaptive behaviour was possible in three individuals with Marshall–Smith syndrome. Results: Marshall–Smith syndrome individuals have more severe ID, less adaptive behaviour, more impaired speech and less reciprocal interaction compared with individuals with Malan syndrome. Sensory processing difficulties occur in both syndromes. Follow‐up measurement of cognition and adaptive behaviour in Marshall–Smith syndrome shows different individual learning curves over time. Conclusions: Results show significant between and within syndrome variability. Different NFIX variants underlie distinct clinical phenotypes leading to separate entities. Cognitive, adaptive and sensory impairments are common in both syndromes and increase the risk of challenging behaviour. This study highlights the value of considering behaviour within developmental and environmental context. To improve quality of life, adaptations to environment and treatment are suggested to create a better person‐environment fit.